New generation implantable cardiac rhythm devices allow safe radiotherapy treatments: A large single centre study. Issue 2 (2018) - Gulletta, Simone; Matta, Mario; Dall'Oca, Italo; D'Angelo, Giuseppe; Gigli, Lorenzo; Radinovic, Andrea; Cireddu, Manuela; Marzi, Alessandra; Sala, Simone; Muzio, Nadia Di; Bella, Paolo Della; Vergara, Pasquale
No abstract available